Professionalism of Competence, Professional Allowance, and The Influ-ence Toward Teacher Performance - Mamik Pristiwindari; Eka Askafi; Ratna Dewi Mulyaningtiyas (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The teacher should become a facilitator in the learning process and has the right to carry out assessments as evidence of the success of the learning process that has been carried out. The teacher's basic ability is very influential on his performance. The performance of a teacher is also not only influenced by one factor, other influences greatly affect his performance. Factors that can influence teacher performance include the provision of professional allowances and professional competence. The research conducted this time has the aim of knowing whether professional competence and the provision of professional allowances together influence teacher performance. The research method uses quantitative methods to analyze the influence of professional competence and professional allowances on teacher performance. Together, professional competence and professional allowances influence teacher performance.